Hubungan Pengetahuan Ibu Tentang IMD Dengan Pelaksanaan IMD di BPM Wenny Bagan Batu Riau - Indah Yani Tambunan (Jurnal Anestesi, 2023)
Early Initiation of Breastfeeding (IMD) is the process of a baby breastfeeding immediately after birth, where the baby is allowed to look for the mother's nipple on its own (not offered to the nipple). Early initiation of breastfeeding will greatly help in the continuation of exclusive breastfeeding (breast milk only) and the duration of breastfeeding. In this way, the baby's needs will be met until the age of 2 years, and prevent children from being malnourished.. Knowing the mother's knowledge about early breastfeeding initiation towards the implementation of IMD at BPM Wenny Bagan Batu Riau in 2022. The population in this study is all mothers who gave birth in January until April - July 2022 at BPM Wenny Bagan Batu Riau there were 54 people and the sample in this study was obtained using total sampling (the entire population was sampled) of 54 people. The chi square test results show that there is a relationship between knowledge and IMD implementation (p=0.001). This is supported by research results (Hidayat, 2016) that the level of knowledge has a significant relationship with the implementation of IMD with a significance figure of p = 0.029 and an RR of 1.615, which means that the rate of implementation of IMD in the group with a high level of knowledge is 1.6 times higher than the group with a low level of knowledge. This means that it can influence someone in doing or carrying out something, specifically implementing IMD.